Accounting Information System for Village Government Fraud Prevention: Tri Kaya Parisudha Moderation - Iswari, I Gusti Ayu Indira; Sanjaya, I Gusti Ngurah; Trisnadewi, A. A. Ayu Erna (PT Keberlanjutan Strategis Indonesia, 2026)
The government increases the village fund budget every year. Good village fund budget management can reduce the risk of adverse conditions. However, field facts actually show an increase in corruption along with the increasing amount of the village fund budget. This study aims to examine the effect of the Accounting Information System on Fraud Prevention with Tri Kaya Parisudha as a moderator in village governments in Banjarangkan District. This study was conducted in 13 villages in Banjarangkan District with a sample of 103 respondents determined using the saturated sampling method. Data were collected by distributing questionnaires to respondents and processed using SPSS 26 with a moderated regression analysis method. Data processing resulted in the accounting information system having a negative and significant effect on accident prevention in village governments in Banjarangkan District. Tri Kaya Parisudha strengthens the influence of the accounting information system on preventing conditions.